KILKA UWAG O ZNACZENIU III STATUTU LITEWSKIEGO W GALICJI - Godek, Sławomir (Zeszyty Prawnicze, 2017)
Some Observations on the Significance of the III Lithuanian Statute in Galicia Summary The Lviv National Vasyl Stefanyk Scientific Library of Ukraine holds a manuscript entitled “Zbiorowa treść Statutu litewskiego jako prawa obowiązującego w prowincjach polskich pod panowaniem rosyjskim będących” (The Collected Content of the Lithuanian Statute: The Law in Force in the Polish Provinces now under Russian Rule”). It was compiled in 1820 by Wacław Michał Mieczkowski, a judge of the Tarnopol (Ternopil) Oblast’. The way the material was arranged in this document helped users find their way around the mass of provisions in the Statute. Mieczkowski’s compilation suggests further research should be done on the role of the Lithuanian Statute with respect to other sources of the law in Austrian Galicia.